Multiple Antimicrobial Resistance in Methicillin-Resistant Staphylococcus sciuri Group Isolates from Wild Ungulates in Spain - Joaquín Rey Pérez; Laura Zálama Rosa; Alfredo García Sánchez; Javier Hermoso de Mendoza Salcedo; Juan Manuel Alonso Rodríguez; Rosario Cerrato Horrillo; Sofía Gabriela Zurita; María Gil Molino (MDPI AG, 2021)
The aim of this study was to investigate the presence of methicillin-resistant Staphylococcus (MRS) strains in non-managed wild ungulates present in a typical Mediterranean forest in Spain. For this purpose, nasal swabs were obtained from 139 animals: 90 wild boar (Sus scrofa), 42 red deer (Cervus elaphus) and 7 fallow deer (Dama dama), which were subsequently pre-enriched in BHI+ NaCl (6.5%) (24 h/37 °C), and then seeded in Columbia blood agar (24 h/37 °C)). The presence of the mecA gene was investigated by PCR, first from the confluent and then from individual colonies. A total of 10 mecA+ colonies were obtained of which only seven showed phenotypic resistance to oxacillin/cefoxitin (methicillin resistance). All MRS strains belonged to the Staphylococcus sciuri group. Methicillin-resistant Staphylococcus aureus (MRSA) was not detected. In addition, a significant number of MRS strains showed resistance to other antimicrobials, mainly β-lactam (7/7), gentamicin (7/7), fusidic acid (6/7) and quinupristin-dalfopristin (6/7), showing an irregular correlation with their coding genes. The genetic profiles grouped the seven strains obtained according to the bacterial species but not in relation to the animal source or the geographical place of origin. The presence of SCCmec type III, common to animals and humans, has been detected in three of the strains obtained. In conclusion, the study reveals that the wild ungulates investigated play a role as potential reservoirs of multi-resistant strains of MRS. Such strains, due to their characteristics, can be easily transferred to other wild or domestic animal species and ultimately to humans through their products.